Stormwater loadings of antibiotic resistance genes in an urban stream. (15th October 2017) - Garner, Emily; Benitez, Romina; von Wagoner, Emily; Sawyer, Richard; Schaberg, Erin; Hession, W. Cully; Krometis, Leigh-Anne H.; Badgley, Brian D.; Pruden, Amy
Abstract: Antibiotic resistance presents a critical public health challenge and the transmission of antibiotic resistance via environmental pathways continues to gain attention. Factors driving the spread of antibiotic resistance genes (ARGs) in surface water and sources of ARGs in urban stormwater have not been well-characterized. In this study, five ARGs ( sul 1, sul 2, tet (O), tet (W), and erm (F)) were quantified throughout the duration of three storm runoff events in an urban inland stream. Storm loads of all five ARGs were significantly greater than during equivalent background periods. Neither fecal indicator bacteria measured ( E. coli or enterococci) was significantly correlated with sul 1, sul 2, or erm (F), regardless of whether ARG concentration was absolute or normalized to 16S rRNA levels. Both E. coli and enterococci were correlated with the tetracycline resistance genes, tet (O) and tet (W). Next-generation shotgun metagenomic sequencing was conducted to more thoroughly characterize the resistome (i.e., full complement of ARGs) and profile the occurrence of all ARGs described in current databases in storm runoff in order to inform future watershed monitoring and management. Between 37 and 121 different ARGs were detected in each stream sample, though the ARG profiles differed among storms. This study establishes that storm-driven transport of ARGs comprises a considerable fraction of overall downstream loadings and broadly characterizes the urban stormwater resistome to identify potential marker ARGs indicative of impact. Graphical abstract: Image 1 Highlights: Storm-driven transport of antibiotic resistance genes (ARGs) was characterized. As many as 121 different ARGs were detected in a single urban stream sample. Loading of all monitored ARGs increased during conditions of storm runoff. ARGs in runoff did not exhibit a "first flush" pattern.